(untitled) (Journal of Contemporary Educational Policies and Practices, 2023)
In recent years, online teaching has gained significant traction in higher education institutions across the globe, primarily due to the widespread impact of the Covid-19 pandemic. Before the pandemic, online teaching was mainly associated with distance learning which aims to provide further education for in-service learners. In this context, our study aims to explore the pedagogical obstacles encountered by Vietnamese university teachers when implementing online teaching in social sciences. Employing qualitative research methods, such as snowball sampling and semi-structured in-depth interviews, the researchers gathered data from 23 university teachers specializing in social sciences across 12 public and private universities in Ho Chi Minh City, Vietnam. The findings of this investigation shed light on various pedagogical barriers that impede the teaching process, encompassing aspects such as lesson plan preparation, lecture delivery (limited interactions, teaching methods and activities, students’ distraction and passive participation, managing virtual classrooms), student assessment, and overall teaching ineffectiveness. This study contributes to the existing literature on contextualized online instructions in higher education, specifically focusing on the social sciences domain. Furthermore, the discussion delves into the critical points, providing a comprehensive understanding of the challenges faced by educators in the online teaching landscape.